Cultural Aspects and Sustainability in Gastronomic Places: Analysis in Tourist Cities in Brazil and Europe - Macêdo, Ana Cristina Linard; Soares, Jakson Renner Rodrigues; Solla, Xosé Manuel Santos (Revista JRG de Estudos Acadêmicos, 2025)
Introduction: Gastronomic tourism has emerged as an important aspect of cultural tourism, offering authentic experiences that reflect the identity and traditions of a region. In tourist cities, both in Brazil and in Europe, gastronomy plays a crucial role in promoting cultural aspects and implementing sustainable practices. The intersection between culture, sustainability and gastronomy is a field of study that deserves attention, as these dynamics can influence both cultural preservation and sustainable economic development in these regions. Objective: This study aims to analyze the relationship between cultural aspects and sustainability practices in gastronomic venues located in tourist cities in Brazil and Europe. The research seeks to identify how local gastronomy can serve as a vehicle for promoting culture and at the same time fostering sustainable practices, contributing to responsible tourism and the preservation of local resources. Method: To achieve this objective, a scoping review was conducted, which included the analysis of scientific articles, reports from international organizations and case studies published in the last ten years. The scoping review allows mapping the available evidence on the relationship between culture, sustainability and gastronomy in tourism contexts, offering a comprehensive view of the practices and strategies adopted in different regions. Inclusion criteria were established to ensure the relevance of the selected studies, considering aspects such as cultural representativeness, adoption of sustainable practices and impact on local tourism. Results: The review indicated that gastronomic venues in tourist cities in Brazil and Europe use gastronomy as a powerful tool for cultural preservation and promotion of sustainability. In Brazil, the valorization of native ingredients and traditional culinary techniques has proven effective in preserving local cultures, while in Europe, the integration of sustainable production and consumption practices is more consolidated. However, both contexts face challenges, such as the need to balance tourism demand with the preservation of natural and cultural resources, as well as the management of the environmental impact generated by tourism. Final Considerations: This study highlights the importance of gastronomic venues as promoters of culture and sustainability in tourist cities. The practices adopted in both Brazil and Europe show that it is possible to align cultural preservation with sustainable development, as long as appropriate policies and strategies are implemented.